Intravenous Injection of Coronavirus Disease 2019 (COVID-19) mRNA Vaccine Can Induce Acute Myopericarditis in Mouse Model. (18th August 2021) - Li, Can; Chen, Yanxia; Zhao, Yan; Lung, David Christopher; Ye, Zhanhong; Song, Wenchen; Liu, Fei-Fei; Cai, Jian-Piao; Wong, Wan-Man; Yip, Cyril Chik-Yan; Chan, Jasper Fuk-Woo; To, Kelvin Kai-Wang; et al.
Abstract: Background: Post-vaccination myopericarditis is reported after immunization with coronavirus disease 2019 (COVID-19) messenger RNA (mRNA) vaccines. The effect of inadvertent intravenous injection of this vaccine on the heart is unknown. Methods: We compared the clinical manifestations, histopathological changes, tissue mRNA expression, and serum levels of cytokine/chemokine and troponin in Balb/c mice at different time points after intravenous (IV) or intramuscular (IM) vaccine injection with normal saline (NS) control. Results: Although significant weight loss and higher serum cytokine/chemokine levels were found in IM group at 1–2 days post-injection (dpi), only IV group developed histopathological changes of myopericarditis as evidenced by cardiomyocyte degeneration, apoptosis, and necrosis with adjacent inflammatory cell infiltration and calcific deposits on visceral pericardium, although evidence of coronary artery or other cardiac pathologies was absent. Serum troponin level was significantly higher in IV group. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike antigen expression by immunostaining was occasionally found in infiltrating immune cells of the heart or injection site, in cardiomyocytes and intracardiac vascular endothelial cells, but not skeletal myocytes. The histological changes of myopericarditis after the first IV-priming dose persisted for 2 weeks and were markedly aggravated by a second IM- or IV-booster dose. Cardiac tissue mRNA expression of interleukin (IL)-1β, interferon (IFN)-β, IL-6, and tumor necrosis factor (TNF)-α increased significantly from 1 dpi to 2 dpi in the IV group but not the IM group, compatible with presence of myopericarditis in the IV group. Ballooning degeneration of hepatocytes was consistently found in the IV group. All other organs appeared normal. Conclusions: This study provided in vivo evidence that inadvertent intravenous injection of COVID-19 mRNA vaccines may induce myopericarditis. Brief withdrawal of syringe plunger to exclude blood aspiration may be one possible way to reduce such risk. Abstract : Intravenous injection of coronavirus disease 2019 (COVID-19) messenger RNA (mRNA) vaccine may induce gross and histopathological changes of acute myopericarditis in Balb/c mice.